DNA Fingerprinting: Advancements and Future Endeavors (Springer Singapore, 2018)
This book describes the basics and various applications of DNA fingerprinting, including in actual case studies. The book is divided in four modules; Module 1: Basics of DNA Fingerprinting, Module 2: Applications of DNA Fingerprinting, Module 3: DNA Fingerprinting: Case Studies, and Module 4: Future of DNA Fingerprinting. Each module consists of 4 to 5 chapters, written by reputed researchers, academics and forensic scientists from around the globe. The respective chapters cover e.g. related fields, the tools and techniques used, various genotyping kits, real-world case studies, ancient DNA and wild life forensics, molecular diagnosis of human diseases, legal aspects, microbial forensics and the economics of the DNA fingerprinting technique. The book offers a practical guide for professionals, graduate and post-graduate students in the fields of Forensic Science, Medicine, Genetics, Anthropology, Microbiology, and Zoology. It also serves as a useful reference resource, summarizing major technological advances in the field of DNA fingerprinting, the problems faced in this field of science and possible new solutions to these problems. Presently, DNA fingerprinting is utilized in solving the majority of criminal cases; as such, the book is also helpful for investigating agencies, as it includes representative case studies.